The Effect of Fumigation and Alkalization on Dimensional Changes of Cantula Fiber Reinforced Unsaturated Polyester Composites Under Immersion - Wibowo, M. Ihsan Tri; Ariawan, Dody; Surojo, Eko (Universitas Sebelas Maret, 2022)
This study investigates the effect of fumigation and alkaline treatment on dimensional change in cantala fibers reinforced Unsaturated Polyester Resins (UPRs) composite under immersion test in an aqueous environment. Composites were fabricated using the compression molding method with cantala fiber content of 30% vt with the addition of 5% microcrystalline cellulose. Composite specimens were immersed under aquades for two months at room temperature. The dimensional changes of cantala fiber-reinforced UPRs in different solutions followed a Fickian behavior. The dimensional change of composites in solution shows the saturation point after several weeks of immersion. Fumigation-treated fibers and alkali-treated fiber composites after immersion have lower results in dimensional changes and slope than untreated fiber composites.